USING A DIDACTIC TOOL WITH IT-SUPPORT FOR TEACHING GEOGRAPHY IN A SPECIAL SCHOOL IN SLOVAKIA - Viktor Hladush; Slávka Bendíková; Barbora Kovačova; Marcela Čarnická (Інформаційні технології і засоби навчання)
The article tells about the peculiarities of using electronic didactic tools in teaching special school students in Slovakia. The staff of the Department of Special Pedagogy, Catholic University in Ruzomberk (Slovakia), together with teachers of special schools prepared a didactic manual with IT support considering the modern requirements for the level of knowledge and skills of students with intellectual disabilities. The purpose of the manual was to increase the level of success in learning geography. The content of the didactic guide is based on the typical curriculum for 9th grade students of a special school approved by the Ministry of Education and Science of Slovakia. As an example, the article briefly highlights the essence of the preparatory stage and the specific sequence of the teacher's work when studying one section «Slovakia». In the course of preparing the didactic guide, the peculiarities of psychophysical development of children in special schools, the problems of perception and understanding of new educational information were taken into account. To showcase the effectiveness of our innovative approach, we conducted an experimental test using the developed electronic textbook with IT support in one of the special schools in Slovakia. During this study, we analyzed and compared the level of geography knowledge among students over a span of 6 academic years (2016 – 2018 – traditional education, 2019 – 2021 – education using e-Learning). Based on the statistical data, a noteworthy improvement in academic performance was observed. To validate these results, considering the limited research sample due to the unique nature of special schools' educational process, we employed nonparametric tests such as the Kruskal-Wallis and Dunn's tests for multiple comparisons. These tests were utilized to ensure the reliability and significance of the findings. The results of the mathematical processing of the materials convincingly confirmed a significant increase in the level of academic achievement over the six years of the educational process in a special school. Thus, the electronic didactic guide for studying geography by 9th grade students of special schools proved to be quite effective. The idea of preparing and using such a didactic guide can be used in practice by teachers of other social studies subjects in special schools.